The globular cluster system of NGC1316 : III. Kinematic complexity - Richtler, Tom (2014)
Context. The merger remnant NGC 1316 (Fornax A) is one of the most important objects regarding the investigation of and thus an important object to study merger-related processes. A recent photometric study used globular clusters in NGC 1316 to constrain its star formation history, but without the knowledge of individual radial velocities. The kinematical properties of the globular cluster system in comparison with the diffuse stellar light might give more insight into the formation of NGC 1316. Of particular interest is the dark matter content. Planetary nebulae in NGC 1316 indicate a massive dark halo, and globular cluster velocities provide independent evidence. Aims. We aim at measuring radial velocities of globular clusters in NGC 1316. We use these kinematical data to investigate the global structure of NGC 1316 and to constrain the dark matter content. Methods. We perform multiobject spectroscopy with VLT/FORS2 and MXU. Out of 562 slits, we extract radial velocities for 177 globular clusters. Moreover, we measure radial velocities of the integrated galaxy light, using slits with a sufficiently bright sky. To these data, we add 20 cluster velocities from the literature. In an appendix, we identify new morphological features of NGC 1316 and its companion galaxy NGC 1317. Results. The GC sample based on radial velocities confirms the colour peaks already found in our photometric study. The bright clusters, which probably have their origin in a 2 Gyr old starburst and younger star formation events, avoid the systemic velocity. A Gaussian velocity distribution is found only for clusters fainter than about mR = 22 mag. The velocity distribution of clusters shows a pronounced peak at 1600 km s-1. These clusters populate a wide area in the south-western region which we suspect to be a disk population. Globular clusters or subsamples of them do not show a clear rotation signal. This is different from the galaxy light, where rotation along the major axis is discernable out to 3′ radius. The kinematic major axis of NGC 1316 is misaligned by about 10° with the photometric major axis, which might indicate a triaxial symmetry. A simple spherical model like that suggested by dynamical analyses of planetary nebulae also reproduces the velocity dispersions of the faint globular clusters. Conclusions. The central dark matter density of the present model resembles a giant elliptical galaxy. This contradicts population properties which indicate spiral galaxies as pre-merger components. Modified Newtonian dynamics (MOND) would provide a solution, but the kinematical complexity of NGC 1316 does not allow a really firm conclusion. However, NGC 1316 might anyway be a problem for a cold dark matter scenario, if the high dark matter density in the inner region is confirmed in future studies.